Optimized cell systems for the investigation of hepatitis C virus E1E2 glycoproteins. (4th January 2021) - Kalemera, Mphatso D.; Capella-Pujol, Joan; Chumbe, Ana; Underwood, Alexander; Bull, Rowena A.; Schinkel, Janke; Sliepen, Kwinten; Grove, Joe
Abstract : Great strides have been made in understanding and treating hepatitis C virus (HCV) thanks to the development of various experimental systems including cell-culture-proficient HCV, the HCV pseudoparticle system and soluble envelope glycoproteins. The HCV pseudoparticle (HCVpp) system is a platform used extensively in studies of cell entry, screening of novel entry inhibitors, assessing the phenotypes of clinically observed E1 and E2 glycoproteins and, most pertinently, in characterizing neutralizing antibody breadth induced upon vaccination and natural infection in patients. Nonetheless, some patient-derived clones produce pseudoparticles that are either non-infectious or exhibit infectivity too low for meaningful phenotyping. The mechanisms governing whether any particular clone produces infectious pseudoparticles are poorly understood. Here we show that endogenous expression of CD81, an HCV receptor and a cognate-binding partner of E2, in producer HEK 293T cells is detrimental to the infectivity of recovered HCVpp for most strains. Many HCVpp clones exhibited increased infectivity or had their infectivity rescued when they were produced in 293T cells CRISPR/Cas9 engineered to ablate CD81 expression (293T CD81KO ). Clones made in 293T CD81KO cells were antigenically very similar to their matched counterparts made parental cells and appear to honour the accepted HCV entry pathway. Deletion of CD81 did not appreciably increase the recovered titres of soluble E2 (sE2). However, we did, unexpectedly, find that monomeric sE2 made in 293T cells and Freestyle 293-F (293-F) cells exhibit important differences. We found that 293-F-produced sE2 harbours mostly complex-type glycans whilst 293T-produced sE2 displays a heterogeneous mixture of both complex-type glycans and high-mannose or hybrid-type glycans. Moreover, sE2 produced in 293T cells is antigenically superior; exhibiting increased binding to conformational antibodies and the large extracellular loop of CD81. In summary, this work describes an optimal cell line for the production of HCVpp and reveals that sE2 made in 293T and 293-F cells are not antigenic equals. Our findings have implications for functional studies of E1E2 and the production of candidate immunogens.